A self‐comfort oriented pattern of regulatory behavior and avoidant attachment are more likely among infants born moderate‐to‐late preterm - Fuertes, Marina (2021)
Infants born preterm (<37 gestational weeks, GW) are at increased risk for regulatory difficulties and insecure attachment. However, the association between infants' regulatory behavior patterns and their later attachment organization is understudied in the preterm population. We addressed this gap by utilizing a Portuguese sample of 202 mother-infant dyads. Specifically, we compared the regulatory behavior patterns of 74 infants born moderate-to-late preterm (MLPT, 32-36 GW) to those of 128 infants born full-term (FT, 37-42 GW) and evaluated the associations of these regulatory patterns with later attachment. Infants' regulatory behavior patterns (Social-Positive Oriented, Distressed-Inconsolable, or Self-Comfort Oriented) were evaluated in the Face-to-Face-Still-Face paradigm at 3 months, and their attachment organization (secure, insecure-avoidant, or insecure-ambivalent) was evaluated in the Strange Situation at 12 months corrected age. In both samples, the Social-Positive-Oriented regulatory pattern was associated with secure attachment; the Distressed-Inconsolable pattern with insecure-ambivalent attachment; and the Self-Comfort-Oriented pattern with insecure-avoidant attachment. However, compared to FT infants, infants born MLPT were more likely to exhibit a Self-Comfort-Oriented pattern and avoidant attachment. Most perinatal and demographic variables were not related to infant outcomes. However, infants with a higher 1-min Apgar were more likely to exhibit the Social-Positive-Oriented regulatory pattern and secure attachment.